1978
DOI: 10.1111/j.1471-0528.1978.tb15827.x
|View full text |Cite
|
Sign up to set email alerts
|

Water Relations of the Ovarian Cycle

Abstract: Summary This study reports the likely pattern of change in serum osmolality during the normal ovarian cycle, together with that which occurs during ovulation‐induction by gonadotrophin. The variation in serum osmolality is attributed to the action of oestrogen on venous distensibility, and the effect of that response on the osmotic equilibrium between intra‐ and extravascular fluid. Although the action of gonadotrophin is mediated by the products of follicular theca and granulosa cells, the physiological respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1979
1979
2000
2000

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The reliability of the hydrostatic weighing technique has been reported to range between r = .92 tor= .99 (Katch, Michael and Horvath, 1967, Sinning, 1977, Wilmore, 1983, Lohman, 1981. However, such reliability estimates have been made on male subjects only and over short periods Throughout the course of the menstrual cycle many women gain weight temporarily due to water retention or other mechanisms (Good, 1978, Dalvit, 1981, Thorn, Nelson and Thorn, 1938. Research has shown that variations in hydration do influence the measurement of density by hydrostatic weighing, thus causing variation in computed estimates of percent fat, fat weight, and fat free weight Romero, 1977, Thomas andEtheridge, 1979).…”
mentioning
confidence: 99%
“…The reliability of the hydrostatic weighing technique has been reported to range between r = .92 tor= .99 (Katch, Michael and Horvath, 1967, Sinning, 1977, Wilmore, 1983, Lohman, 1981. However, such reliability estimates have been made on male subjects only and over short periods Throughout the course of the menstrual cycle many women gain weight temporarily due to water retention or other mechanisms (Good, 1978, Dalvit, 1981, Thorn, Nelson and Thorn, 1938. Research has shown that variations in hydration do influence the measurement of density by hydrostatic weighing, thus causing variation in computed estimates of percent fat, fat weight, and fat free weight Romero, 1977, Thomas andEtheridge, 1979).…”
mentioning
confidence: 99%